The Last of the Barons $1 (BCompletes - Lytton, Edward Bulwer Lytton, Baron, 1803-1873 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Last of the Barons $1 (BComplete" by Edward Bulwer Lytton is a historical novel written in the mid-19th century. The book weaves a narrative set during the reign of Edward IV of England, focusing particularly on the dynamics of the powerful and influential Earl of Warwick, known as the King-maker. Through the lens of Warwick's life and his complex relationship with King Edward IV, the story explores themes of power, loyalty, and the shifting alliances during the tumultuous period of the Wars of the Roses. The opening of the novel introduces readers to a vibrant scene at a holiday festival in early spring of 1467, where citizens gather for archery competitions. It sets the stage for the complexities of social class and rivalry between nobles and the burgeoning middle class. Characters such as Nicholas Alwyn, a humble trader, and Marmaduke Nevile, a nobleman, are established, highlighting the contrasting perspectives of the time. Furthermore, we meet Sibyll Warner, a scholar$1 (Bs daughter, who faces ridicule but exhibits a strong character. Through these characters, the novel hints at the intricate interplay of personal ambition, social upheaval, and the powerful figures like Warwick, who will significantly impact the historical landscape. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Last_of_the_Barons
Release date is 2004-11-26
Produced by Tapio Riikonen and David Widger
Keywords: Great Britain -- History -- Wars of the Roses, 1455-1485 -- Fiction; Warwick, Richard Neville, Earl of, 1428-1471 -- Fiction